Towards new ways of thinking about territory: a proposal for the development of the Gran La Plata region, Buenos Aires, Argentina - Mariana Birche; Rocío Rodríguez Tarducci; Karina Jensen; María Elisa Cremaschi; Pilar Bilbao; Olga Ravella (Cuaderno Urbano, 2021)
This article deals with analyzing the development of the La Plata Region from its foundation to the present, to propose alternative aimed at mitigating the effects caused by unsustainable urban development. For this, the principles considered as "sustainable" are discussed and it is investigated how their application can become a strategy for approaching sustainable development, in the context of the current technical-economic and socio-environmental paradigm. As a result of the research, alternative development proposals are conceived from the various investigations carried out by the authors in the last twenty years.